Strategi Kampanye Kreatif Untuk Meningkatkan Penjualan: Studi Kasus Toko Sepatu dan Sandal Needshoes - Ahmad Nadhim Musyarof; Agus Wahyudi; Daniel Budiyanto; Mochammad Daffa Esta Firdaus (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
In an era of increasingly fierce business competition, creative and innovative marketing strategies are an important factor to attract consumer attention and encourage sales. This article presents a case study from a shoe and sandal shop NeedShoes which succeeded in improving its business performance through a unique and interesting creative campaign. Using historical methods, literature studies, and case studies, this article explores the background of the shoe and sandal retail industry, analyzes NeedShoes' creative campaigns in depth, and identifies success factors, challenges, and valuable lessons that can be adopted by other businesses.